Liberia : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
This paper discusses implementation of the Poverty Reduction Strategy (PRS) in Liberia. Liberia's PRS articulates the government's overall vision and major strategies for moving toward rapid, inclusive, and sustainable growth and development during the period 2008-11. This paper provides the context for the PRS by describing the conflict and economic collapse, the transition beyond conflict, and the initial progress achieved during the past two years. It stresses that Liberia must create much greater economic and political opportunities for all its citizens and ensure that growth and development are widely shared.